Cyanophycin Synthesis Optimizes Nitrogen Utilization in the Unicellular Cyanobacterium Synechocystis sp. Strain PCC 6803 - Watzer, Björn (Appl Environ Microbiol, 2018)
Cyanophycin is a carbon/nitrogen storage polymer widely distributed in most cyanobacterial strains and in a few heterotrophic bacteria. It is a nonribosomal polypeptide consisting of equimolar amounts of aspartate and arginine. Here, we focused on the physiological function and cell biology of cyanophycin in the unicellular nondiazotrophic cyanobacterium Synechocystis sp. strain PCC 6803. To study the cellular localization of the cyanophycin-synthesizing enzyme CphA during cyanophycin synthesis and degradation, we fused it to green fluorescent protein. When CphA was inactive, it localized diffusely in the cytoplasm. When cyanophycin synthesis was triggered, CphA first aggregated into foci and later localized on the surface of cyanophycin granules. In the corresponding cell extracts, localization of CphA on the cyanophycin granule surface required Mg(2+). During cyanophycin degradation, CphA dissociated from the granule surface and returned to its inactive form in the cytoplasm. To investigate the physiological role of cyanophycin, we compared wild-type cells with a CphA-deficient mutant. Under standard laboratory conditions, the ability to synthesize cyanophycin did not confer a growth advantage. To mimic the situation in natural habitats, cells were cultured with a fluctuating and limiting nitrogen supplementation and/or day/night cycles. Under all of these conditions, cyanophycin provided a fitness advantage to the wild type over the mutant lacking cyanophycin. During resuscitation from nitrogen starvation, wild-type cells accumulated cyanophycin during the night and used it as an internal nitrogen source during the day. This demonstrates that cyanophycin can be used as a temporary nitrogen storage to uncouple nitrogen assimilation from photosynthesis. IMPORTANCE We clarified the elusive biological function of cyanophycin in the nondiazotrophic cyanobacterium Synechocystis sp. PCC 6803. Cyanophycin is a dynamic carbon/nitrogen storage polymer (multi-arginyl-l-polyaspartate) that is conditionally present in most cyanobacteria and a few heterotrophic bacteria as cellular inclusion granules. Here, we show that the cyanophycin-synthesizing enzyme CphA in the nonactive state localizes diffusely in the cytoplasm. When cyanophycin synthesis is triggered, active CphA first aggregates into foci and then covers the surface of mature cyanophycin granules, which in vitro requires Mg(2+) as a cofactor. Cyanophycin accumulation enables Synechocystis sp. to optimize nitrogen assimilation under nitrogen-poor conditions, in particular when the nitrogen supply fluctuates and during day/night cycles, by allowing continuous nitrogen assimilation and storage. Therefore, cyanophycin provides the wild-type cyanobacterium with a clear fitness advantage over non-cyanophycin-producing cells in natural environments with fluctuating nitrogen supply.